Gut microbiota offers new insight into public health - I Nengah Sujaya (Universitas Udayana, 2020)
With the increasing scientific evidence of the contribution of GM to health and disease, various approaches are sought to maintain, restore or modulate the groups of beneficial bacteria in the digestive tract. Those approaches are mainly performed through three different ways including administration of probiotics, prebiotics, and fecal microbial transplantation. The probiotic approach is commonly attained through the consumption of live bacteria which can improve the health of the host, while prebiotic approach is the consumption of food ingredients or food components that increase the growth of beneficial bacteria inthe digestive tract. Meanwhile, fecal microbial transplantation (FMT) has been beginning to perform under certain conditions in which fecalmicrobiota is introduced into individuals with certain disease and has been showing encouraging results. Even though the application of probiotics (bacteriotherapy) in maintaining or modulating of GM yet to fully recognized by some countries, the approach has showed positive impact on humanhealth demonstrated in certain diseases prevention. Similar evidence was obtained from studies that revealed the beneficial outcomes of prebiotic and FMT intervention for human GM, which consequently improve human health. Therefore, it is noticeable that the composition of GM is a promising aspect which may need to be considered in developing an innovative intervention program to alleviate certain public health problem.